Characterizing the entrepreneurial profile of university students from a developing country - D'Armas Regnault, Mayra; Mejías Acosta, Agustín; Noboa Romero, Pedro; Fajardo Vaca, Ligia; Álvarez Baque, Wellington; Vidal-Silva, Cristian (Frontiers in Education, 2024)
Entrepreneurship serves as a pivotal force for innovation and sustainable development. Today, its influence on wealth generation, job creation, and national economic growth is indisputable. Understanding the entrepreneurial profiles and capacities of future professionals has become a priority within both academic and business realms. While there is substantial research evidence highlighting the impact of entrepreneurship on the business sector, studies specifically examining university contexts worldwide are limited, particularly in developing nations. This study aimed to characterize the entrepreneurial capacity profile of university students in Ecuador, a developing country in South America. Drawing from a literature review, we developed an instrument adapted from the theory of planned behavior (TPB), incorporating personal attitude, subjective norms, and perceived behavioral control as determinants of entrepreneurial intention. This framework measures entrepreneurial capacity, integrating prominent entrepreneurial competencies identified in the literature as part of personal factors: problem-solving, creativity, financial management, leadership, negotiation, decision-making, self-confidence, and resilience. The instrument was administered to a sample of university students in Ecuador. Using statistical methods, we analyzed the relationships between demographics (age and gender), educational background (parents' education and occupation), the entrepreneurial ecosystem, and TPB factors-including personal attitude, subjective norms, and perceived behavioral control-on entrepreneurial intention. Key findings reveal that age, gender, parents' educational background, occupation, and the entrepreneurial ecosystem significantly influence the entrepreneurial intentions of university students. Within their entrepreneurial profiles, self-confidence, creativity, and decision-making skills emerged prominently, while financial management, negotiation, and problem-solving showed potential areas for development. These results offer valuable insights for updating academic programs to foster entrepreneurial intention in Ecuador and other developing countries. Theoretically, this study reinforces TPB as a foundational framework in entrepreneurship research, particularly underscoring the moderating role of sociodemographic variables such as age, gender, and educational level. Practically, it provides a quantitative measurement tool and a control variable for future studies aiming to identify entrepreneurial skills within regional contexts.